1987
DOI: 10.1200/jco.1987.5.2.286
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant alfa interferon in renal cell carcinoma: a randomized trial of two routes of administration.

Abstract: Ninety-seven patients with recurrent or metastatic renal cell carcinoma were randomized to receive recombinant interferon (IFN) alfa-2b (Intron A; Schering-Plough, Kenilworth, NJ) by either the subcutaneous (SC) or intravenous (IV) route. The SC dosage was 2 X 10(6) IU/m2 three times weekly, and the IV dose 30 X 10(6) IU/m2 for five consecutive days every 3 weeks. Dose escalation to a maximum of 10 X 10(6) IU/m2 SC and 50 X 10(6) IU/m2 IV was allowed for patients with minimal or absent toxicity. Five of 51 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(40 citation statements)
references
References 4 publications
2
37
1
Order By: Relevance
“…However, with the introduction of immunotherapy (eg, IFNa, interleukin-2), multiple retrospective series suggested that survival could be improved with the use of CN in highly selected patients before immunotherapy. 9,[15][16][17][18][19][20][21][22][23] One study by Fallick et al demonstrated that, when strict criteria were applied (eg, >75% debulking of tumor, clear cell histology, an Eastern Cooperative Oncology Group [ECOG] performance status of 0 or 1, and the absence of central nervous system, bone, or liver metastasis), the median survival was 20.5 months, and >90% of patients were able to receive adjuvant interleukin-2 therapy. 9 More important, a combined analysis of 2 randomized trials (European Organization for the Research and Treatment of Cancer trial 30947 and Southwest Oncology Group trial 8949) that examined patients with mRCC who either received IFNa alone or underwent nephrectomy followed by IFNa demonstrated that the median OS was longer in patients who underwent nephrectomy compared with patients who received IFNa alone (13.6 months; 95% confidence interval [CI], 9.7-17.4 months; vs 7.8 months; 95% CI, 5.9-9.7 months; hazard ratio [HR], 0.69; 95% CI, 0.55-0.87; P ¼ .002).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the introduction of immunotherapy (eg, IFNa, interleukin-2), multiple retrospective series suggested that survival could be improved with the use of CN in highly selected patients before immunotherapy. 9,[15][16][17][18][19][20][21][22][23] One study by Fallick et al demonstrated that, when strict criteria were applied (eg, >75% debulking of tumor, clear cell histology, an Eastern Cooperative Oncology Group [ECOG] performance status of 0 or 1, and the absence of central nervous system, bone, or liver metastasis), the median survival was 20.5 months, and >90% of patients were able to receive adjuvant interleukin-2 therapy. 9 More important, a combined analysis of 2 randomized trials (European Organization for the Research and Treatment of Cancer trial 30947 and Southwest Oncology Group trial 8949) that examined patients with mRCC who either received IFNa alone or underwent nephrectomy followed by IFNa demonstrated that the median OS was longer in patients who underwent nephrectomy compared with patients who received IFNa alone (13.6 months; 95% confidence interval [CI], 9.7-17.4 months; vs 7.8 months; 95% CI, 5.9-9.7 months; hazard ratio [HR], 0.69; 95% CI, 0.55-0.87; P ¼ .002).…”
Section: Discussionmentioning
confidence: 99%
“…Most responses are partial and short-lived (median response duration, 6 to 7 months). Approximately 2% of patients have had complete responses, with only an occasional patient having a response persistence in excess of 1 year after therapy (9). Although no clear dose-response relationship exists, thrice weekly doses in the 5-to 10-MU/M 2 range appear to have the highest therapeutic index.…”
Section: Interferon ␣mentioning
confidence: 99%
“…22,23 Although IFN-a has produced modest benefits in unselected patients, randomized clinical trials have revealed a small survival benefit with manageable toxic effects compared with non-IFN-a control arms. [24][25][26][27][28][29][30][31] Because it became the de facto standard of care worldwide, regulatory agencies have supported the use of IFN-a as the control arm for randomized trials with targeted therapies that are described elsewhere. [15][16][17][18] The results of these investigations, in general, have established the superiority of targeted agents in previously untreated patients, thereby narrowing the future use of IFN-a as a single agent in this setting.…”
Section: Cytokine Therapymentioning
confidence: 99%